Результати експериментальних досліджень МЕЗ-330 «Автотрактор» з плугом ПНН-5-40 - Погорілий, С. П.; Pogorily, S. (ЦНТУ, 2017)
У роботі наведені результати досліджень роботи орного агрегату в складі МЕЗ-330 «Автотрактор» та плуга ПНН-5-40. Наведено методику проведення експериментальних досліджень, вимірювальне обладнання для реєстрації даних та фізико-механічні характеристики фону, на якому проводилися випробування. За результатами випробувань орного агрегату отримано взаємозв’язок між параметрами, зокрема, швидкістю руху, витратою палива та продуктивністю агрегату. Determine the main operational parameters of the arable aggregate based on the MEZ-330 "Autotractor" and the plunger PNN-5-40. The results of researches of work of the arable aggregate in the structure MEZ-330 "Autotractor" and the plunger PNN-5-40 are given in the work. The method of carrying out of experimental researches, measuring equipment for data registration and physical-mechanical characteristics of the background on which the tests were conducted are given. According to the results of tests of the arable aggregate, interconnection was obtained between the parameters, in particular, the speed of movement, fuel consumption and the productivity of the aggregate. According to the results of experimental studies of the arable aggregate MEZ-330 + PNN-5-40, it was established that under the conditions of ensuring the width of capture - 2.1 m, the depth of cultivation - 30 cm, working speed was 7,8 km/h (transfer number 2n ) and 10,8 km/h (transfer number 2v), the wheel hitch did not exceed 8%, the unit's productivity was 1,29 ha/h and 1,78 ha/h respectively, and the fuel consumption was 18,2 l/ha and 19,5 l/ha, which is at the level of arable aggregates formed on the basis of tractors.
Results of experimental research MEZ-330 "Autotractor" with plow PNN-5-40
Keywords: мобільний енергетичний засіб; автотрактор; орний агрегат; коефіцієнт буксування; mobile power tool; autotractor; arable aggregate; loading coefficient